Love in Cold Blood: Are Reptile Owners Emotionally Attached to Their Pets?. (3rd September 2021) - Haddon, Celia; Burman, Oliver H. P.; Assheton, Phil; Wilkinson, Anna
ABSTRACT: A growing number of reptiles are being kept as companion animals in private households, and this has resulted in a concomitant rise in welfare concerns. Poor welfare has been linked to a lack of the emotional attachment in other groups. The aim of this study was to investigate owner attachment to pet reptiles, grouped as lizards, snakes, and tortoises. The Lexington Attachment to Pets Scale (LAPS) questionnaire was administered online to a self-selected sample of 2, 992 adult reptile owners, including 1, 281 owners of both reptiles and dogs. The latter responded first for reptiles and then for dogs. Findings revealed evidence of an emotional attachment toward reptiles that was within the range of those observed in traditional pets. In addition, owners had a stronger attachment to lizards than snakes or tortoises and were also more attached to snakes than tortoises. Owners with both dogs and reptiles showed significantly higher attachment scores to their dogs than to reptiles. However, attachment scores for dogs were higher than those found in other studies. This work reveals strong evidence for a human–reptile attachment and suggests that instances of poor welfare may not result from a lack of attachment but rather a lack of knowledge.